Growth of high-quality wafer-scale graphene on dielectric substrate for high-response ultraviolet photodetector. (30th April 2021) - Chen, Yang; Jiang, Ke; Zang, Hang; Ben, Jianwei; Zhang, Shanli; Shi, Zhiming; Jia, Yuping; Lü, Wei; Li, Dabing; Sun, Xiaojuan
Abstract: Growth of graphene on dielectric substrates is crucial for its use in various electronic and optoelectronic devices, which may avoid the additional extrinsic defects and residual pollution originating from the essential transfer process of graphene grown by chemical vapor deposition on metal foils. However, the growth of high-quality and wafer-scale graphene on dielectric substrates is now still a challenge. Herein, we report the growth of graphene from solid polymer carbon source on various substrates under the assistance of Nickel/SiO2 capping layer. The wafer-scale graphene with excellent uniformity and continuity was achieved on 2 inch sapphire substrates. The dynamics of the graphene growth were proposed, which mainly consist of polymer carbonization, carbon dissolution, segregation and precipitation. The graphene was also grown on undoped GaN to serve as the carrier transport channel of ultraviolet photodetectors, exhibiting a 4 A/W response. The growth of high-quality and wafer-scale graphene on dielectric substrates reported by present work would promote commercial application of the graphene-based electronic and optoelectronic devices. Graphical abstract: Image 1 Highlights: Direct growth of high-quality graphene on dielectric substrates with the Ni/SiO2 capping layer. Wafer-scale graphene with excellent uniformity and continuity on 2 inch sapphire substrates. Dynamics of the direct growth of graphene from solid polymer carbon source. High-response 4 A/W ultraviolet photodetectors based on this graphene directly grown on undoped GaN.